Inverse moving source problem for time-fractional evolution equations: determination of profiles. (12th July 2021) - Liu, Yikan; Hu, Guanghui; Yamamoto, Masahiro
Abstract: This article is concerned with two inverse problems on determining moving source profile functions in evolution equations with a derivative order α ∈ (0, 2] in time. In the first problem, the sources are supposed to move along known straight lines, and we suitably choose partial interior observation data in finite time. Reducing the problems to the determination of initial values, we prove the unique determination of one and two moving source profiles for 0 < α ⩽ 1 and 1 < α ⩽ 2, respectively. In the second problem, the orbits of moving sources are assumed to be known, and we consider the full lateral Cauchy data. At the cost of infinite observation time, we prove the unique determination of one moving source profile by constructing test functions.